End to dream? British retired residents in Spain and their return patterns - Giner-Monfort, Jordi (Journal of Tourism, Sustainability and Well-being, 2018)
Academic production on residential tourism and retirement migration historically focus on movements of arrival in receiving countries. This assumes both the uni-directionality of migrations and the importance of analysing immigrations from the host society point of view. Other types of migratory flows or mobility such as re-emigrations, return movements or transnationalism are left aside from the academic agenda. One of the factors that difficult the analysis of issues such as re-emigration or return migration is the arduousness of capturing these movements in migration statistics. Even when we have access to such sources of information, their interpretation must be very prudent, since numbers do not always reflect real migrations. In this paper, we focus our analysis both on the British population living in Spain, their arrivals and, mainly, out-migrations. Moreover, the result of the referendum of 23th May 2016 could be key to understanding future exit movements. We will use the Residential Variation Statistics (RVS) developed by the National Statistics Institute (INE) to try to shed some light on this topic.